Corporate Governance, Voluntary Disclosure, Earning Quality, Information Asymmetric: A Conceptual Framework - Putra, Danang Adi; Herawansyah; Sriwidharmanelly; Madani Hatta (Open Access Indonesia Journal of Social Sciences, 2023)
There are many factors in financial markets that have different levels of understanding and knowledge in managing available information. With this condition, actors/participants, especially investors, will be informed differently, or there will be information asymmetry in the financial market. This study aimed to develop a conceptual framework that investigates and provides a systematic understanding of the relationship between profit quality, voluntary disclosure, and information asymmetry as single and interaction effects. Furthermore, the study explains the role of corporate governance implementation on the quality of earnings and voluntary disclosure. The explanation of the relationship between the variables studied is based on agency theory with a literature review related to earning quality, voluntary disclosure, information asymmetry, and corporate governance. This conceptual framework illustrates the impact of earning quality and voluntary disclosure on information asymmetry and the role of the interaction between earnings quality and voluntary disclosure of information asymmetry. The results of the literature review present five prepositions that can be formulated in hypotheses to be confirmed. In conclusion, this framework allows researchers and practitioners to investigate further the relationship between variables intended in this research model.